2015
DOI: 10.1149/2.0161602jes
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nickel Titanate-Modified Pt Nanostructured Catalyst for the ORR in Alkaline Media

Abstract: The electrocatalytic performance of novel Pt-NiTiO 3 /C catalyst for the oxygen reduction reaction (ORR) is investigated for the first time. The cathode has been synthesized in a two-step procedure. Firstly, the NiTiO 3 co-catalyst is obtained via a wet-chemical method. Then, 20% Pt-NiTiO 3 /C electrocatalysts (Pt:NiTiO 3 ratio of 1:1 at. %) is prepared by irradiating a mixture of NiTiO 3 , Vulcan and Pt precursor for 4 min in a microwave apparatus. As a reference, a 20% Pt/C catalyst has been synthesized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The recently reported noncarbon-supported Pt catalysts have improved stability but require more investigation. [193][194][195][196][197][198] Meanwhile, atomically dispersed Pt catalysts have attracted more attention due to nearly 100% utilization efficiency, which can minimize the Pt loading in fuel cells. [199] Liu et al [200] and Li et al [201] found that N-doped carbon-supported Pt single atom catalyst exhibited significantly higher ORR activity compared to the conventional Pt/C due to the synergistic effect between Pt and N atoms.…”
Section: Liquid Cell Evaluation Of Pgm-based Electrocatalystsmentioning
confidence: 99%
“…The recently reported noncarbon-supported Pt catalysts have improved stability but require more investigation. [193][194][195][196][197][198] Meanwhile, atomically dispersed Pt catalysts have attracted more attention due to nearly 100% utilization efficiency, which can minimize the Pt loading in fuel cells. [199] Liu et al [200] and Li et al [201] found that N-doped carbon-supported Pt single atom catalyst exhibited significantly higher ORR activity compared to the conventional Pt/C due to the synergistic effect between Pt and N atoms.…”
Section: Liquid Cell Evaluation Of Pgm-based Electrocatalystsmentioning
confidence: 99%
“…4C), slightly smaller Tafel slopes for the MMNCs (32 and 31 mV/decade) were measured, as compared with Pt (37 mV/decade), indicating a similar reaction mechanism in ORR. We also compared our result with the literature data, and our MMNCs are still among best-performing catalysts (SI Appendix, Table S3) (43)(44)(45)(46)(47).…”
Section: Resultsmentioning
confidence: 80%
“…Green and sustainable energy has attracted worldwide attention but the biggest obstacle in adoption and implementation is the efficient conversion and rapid storage of energy. It is generally believed that fuel cells, metal–air batteries, and water splitting are promising energy storage and conversion technologies, which can be a paradigm shift in the adoption and usage of renewable energy compared to fossil fuels. , The oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are two key reactions in fuel cells and metal–air batteries, while the hydrogen evolution reaction (HER) and OER play a significant role in water splitting. Typically, the ORR, OER, and HER reactions use noble metal-based catalysts to improve the reaction rate or optimize the reaction process. For example, Pt-based catalysts are highly effective for ORR and HER catalysis, and Ru- or Ir-based catalysts can be well utilized for the OER. , However, noble metal scarcity, coupled with their lack of multifunctionality in abovementioned three reactions (i.e., Pt cannot be used for both ORR and OER), makes it difficult to develop the large-scale adoption or industrialization of these energy storage technologies . Therefore, it would be greatly advantageous and significant to design multifunctional and low-cost (noble metal-free) catalysts with high activity. , …”
Section: Introductionmentioning
confidence: 99%